Skewness: Important parameter to affect the dielectric properties of BaTiO3 - Jong-Chan Lim; Sang-il Kim; Gyo-Hee Hong; Ji-Hyun Hwang; Heesun Yang; Kyu Hyoung Lee; Hyun-Sik Kim (Journal of Asian Ceramic Societies, 2022)
Recent electric vehicle multilayer ceramic capacitors (MLCCs) adopt submicron-sized solid-state synthesized BaTiO3 for dielectric layers for high reliability. Unlike BaTiO3 nanoparticles synthesized by the hydrothermal method, particle size distribution control becomes demanding with the solid-state synthesis. Here, BaTiO3 with 260 and 390 nm average particle sizes were synthesized using a solid-state method, and the dielectric properties of the samples sintered at 1100, 1150, and 1200°C were studied in terms of particle size distributions. Notably, BaTiO3 samples sintered with 260 nm particles with smaller grain sizes and lower tetragonality exhibited higher dielectric properties than those prepared with 390 nm particles. The reasons behind the high dielectric performance were found in the lower skewness of the 260 nm particles, which produced a higher density of the sintered sample. For electric vehicle MLCC BaTiO3, engineering their skewness is as important as controlling their grain size or tetragonality for high dielectric performance.